Q-switched Erbium-doped Fiber Laser Utilising a Saturable Absorber Based on Brass Nanoparticles - Ganesan, Krishnan; Siti Qistina Arora, Talib; Afiq Arif Aminuddin, Jafry; Sulaiman, Wadi Harun; Muhammad Safwan, Abd Aziz; Mundzir, Abdullah (INTI International University, 2024)
A passively Q-switched erbium-doped fiber laser was successfully demonstrated using brass nanoparticles embedded in Polyvinyl alcohol film as a saturable absorber. The brass nanoparticles were produced by ablating brass target in polyvinyl alcohol solution using Nd:YAG laser. The saturable absorberwas characterised in terms of its morphology, elemental contents and optical properties. It was incorporated into a ring cavity to function as a Q-switcher for generating pulses. As the pump power was varied from 21 mW to 67 mW, the repetition rate increased from 38.74 kHz to 73.75 kHz while the corresponding output pulse width and pulse energy varied from 5.11 μs to 2.473 μs and 69.6 nJ to 145.6 nJ respectively. The output power characterised bytheslope efficiency of 17.72 % and 10.74 mW of output power recorded at 67 mW pump power.